Factors Affecting the Quality of Local Government Financial Statements - Budiyani, Erna Nur; Sinarasri, Andwiani; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of accounting understanding, internal control system, and the use of information technology on the quality of local government financial reports in Semarang City OPD. The population in this study is OPD employees in Semarang City. Meanwhile, the research sample was 88 respondents. Data collection was carried out by distributing questionnaires. The data were analyzed using multiple linear regression analysis. The result of this study is that accounting understanding has a positive and significant effect on the quality of local government financial statements. The internal control system has a positive and significant effect on the quality of local government financial statements. The use of information technology has a positive and significant effect on the quality of local government financial reports. The results of the determination coefficient (R2) show that the understanding of accounting, internal control system, and the use of information technology in explaining the quality of local government financial statements is 62% and the rest is explained by other variables that are not studied in this study.